2013
DOI: 10.7705/biomedica.v34i0.1686
|View full text |Cite
|
Sign up to set email alerts
|

¿Es la resistencia de Mycobacterium leprae a los medicamentos un verdadero motivo de preocupación? Primera aproximación a la vigilancia molecular de pacientes colombianos multibacilares con tratamiento previo para lepra y sin él

Abstract: Introduction:There is no information in Colombia on Mycobacterium leprae primary and secondary drug resistance in regards to the WHO-multidrug therapy regime. On the other hand, public health authorities around the world have issued various recommendations, one of which prompts for the immediate organization of resistance surveillance through simple molecular methods. Objective: To determine the prevalence of Mycobacterium leprae drug resistance to rifampicin, ofloxacin and dapsone in untreated and previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…The multivariate analysis model used showed that none of the demographic or clinical variables influenced the occurrence of drug resistance. The same results were found in studies in Colombia (24), China (25), and India (26). This may indicate that AMR is more related to the inherent characteristics of the bacillus and that it is probably influenced by factors such as irregular use of antimicrobials (27).…”
Section: Discussionsupporting
confidence: 79%
“…The multivariate analysis model used showed that none of the demographic or clinical variables influenced the occurrence of drug resistance. The same results were found in studies in Colombia (24), China (25), and India (26). This may indicate that AMR is more related to the inherent characteristics of the bacillus and that it is probably influenced by factors such as irregular use of antimicrobials (27).…”
Section: Discussionsupporting
confidence: 79%
“…The recurrent case's sample came from a patient who, 40 months before, had completed MDT. The appearance of new clinical signs and the recurrence diagnosis included positive bacillary viability and negative test to drug resistance determined by mutations in the drug resistance-determining region (DRDR) for the folP1, rpo β, and gyrA genes from M. leprae [24].…”
Section: Mycobacterium Leprae Purification From Biopsy Samples Of Pat...mentioning
confidence: 99%
“…Factors influencing recurrence include delayed initial diagnosis, high initial bacillary loads, and leprosy in multibacillary patients [18]. This clinical manifestation differs from processes such as drug resistance and reinfection, the latter in patients who have been cured and years later start the disease again with a new strain of M. leprae [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…[13,25,26] The prior use of FQ was reported in 18 studies (Table 4). [13,[24][25][26]29,[32][33][34][35][36][37][38][39][40][41][42][43][44] Mutations in gyrA (Tables 1, 4) Among the 18 substitutions described in GyrA, nine were inside and seven outside the QRDR, and two were inside the intein (Table 1). The A91 substitution was the most prevalent.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Multiple substitutions in GyrA were found in three strains (Table 4). [29,35,41] Double mutations in gyrA have been described and associated with highlevel resistance. [45] They may result from a two-step selection of FQ-resistant mutants, which unlikely occurs in the extremely slow growing M. leprae.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%